Basic Semiconductor Physics - Hamaguchi, Chihiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents a detailed description of the basic semiconductor physics. The reader is assumed to have a basic command of mathematics and some elementary knowledge of solid state physics. The text covers a wide range of important phenomena in semiconductors, from the simple to the advanced. The reader can understand three different methods of energy band calculations, empirical pseudo-potential, k.p perturbation and tight-binding methods. The effective mass approximation and electron motion in a periodic potential, Boltzmann transport equation and deformation potentials used for full band Monte Carlo simulation are discussed. Experiments and theoretical analysis of cyclotron resonance are discussed in detail because the results are essential to the understanding of semiconductor physics. Optical and transport properties, magneto-transport, two dimensional electron gas transport (HEMT and MOSFET), and quantum transport are reviewed, explaining optical transition, electron phonon interactions, electron mobility. Recent progress in quantum structures such as two-dimensional electron gas, superlattices, quantum Hall effect, electron confinement and the Landauer formula are included. The Quantum Hall effect is presented with different models. In the second edition, the addition energy and electronic structure of a quantum dot (artificial atom) are explained with the help of Slater determinants. Also the physics of semiconductor Lasers is described in detail including Einstein coefficients, stimulated emission, spontaneous emission, laser gain, double heterostructures, blue Lasers, optical confinement, laser modes, strained quantum wells lasers which will give insight into the physics of various kinds of semiconductor lasers, in addition to the various processes of luminescence.
Energy Band Structures of Semiconductors -- Cyclotron Resonance and Energy Band Structures -- Wannier Function and Effective Mass Approximation -- Optical Properties 1 -- Optical Properties 2 -- Electron$1 (BPhonon Interaction and Electron Transport -- Magnetotransport Phenomena -- Quantum Structures -- Light Emission and Laser.s
Keywords: Physics; Computer engineering; Optical materials; Surfaces (Physics).; Physics; Condensed Matter Physics; Electrical Engineering; Optical and Electronic Materials; Characterization and Evaluation of Materials